(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
Heidegger’s enquiry into Being and Dasein can be seen as the foundation for much of existential psychotherapy. Yet different therapists appear to draw on different aspects of Dasein and Heidegger’s work to inform their own therapy. This paper will look at the influence of Heidegger on Spinelli and van Deurzen and consider the differences between the two in terms of their concepts of the ’self’, their emphasis on the ontic and ontological levels and the ’aims’ of their psychotherapeutic approaches.